Pengaruh Frekuensi Konsumsi Makanan Kariogenik Dan Status Gizi Terhadap Status Karies Siswa Sd Negeri Ngadirejo I Usia 7-8 Tahun, Kecamatan Kartasura, Kabupaten Sukoharjo - Rosdiana, Wahyu Dwita; , drg. Ana Riolina, MPH; , drg. Retno Sari (2015)
Cariogenic food is very popular among students and this state could influence the health of children teeth. This kind of food containing a numerous of sucrose which is defined as a major cause of caries occurrence. The thickening of whack on the surface of the tooth happened after 30-60 minutes consuming the food which is containing sucrose, furthermore the streptococcus mutants bacterium would change the mood of sucrose into acid. In the other hand, not only the cariogenic food, the nutritional status can also as a cause of caries occur. The miserable nutritional status would have an impact on the salivary gland function, therefore the prevention of caries would not maximal. The deprivation of essential nutrients substance such as vitamin A, C, D, calsium, phosphorus and fluorine in children could influence the development of teeth, therefore the caries would more susceptible. The aim of this study was to find out the influence of frequency consuming cariogenic food and nutritional status for the caries status among the students between 7- years old in SD Negri 1 Ngadirejo, subdistrict Kartasura, Sukoharjo district. According to the result of Mann Whitney test demonstrated that there was no influence between the frequency of consuming cariogenic food with 0,106 significant number, and there was the influence between nutritional status and caries status with 0,000 significant number.